Unstable Weights in the Combination of Forecasts - Kang, Heejoon (Management Science, 1986)
The weights used in the combination of forecasts are shown to be very unstable. They are generally so unstable that the combined forecasts often do not perform better than some of the individual forecasts or a simple average of the forecasts in practice. The instability is found from a series of Monte Carlo experiments as well as from the nominal GNP forecasts from four well-known macro forecasters. The Monte Carlo experiments also show that when the underlying models are known, a composite forecast from a composite model is generally more accurate than the combination of the individual forecasts. A simple average is shown to be the best technique to use in practice, because the weights in the combination are so unstable.